THU0251 Characteristics of newly diagnosed axial spondyloarthritis patients in rheumatology practices across germany. (12th June 2018) - Poddubnyy, D.; Edelmann, E.; Rios Rodriguez, V.; Sartingen, S.; Mosch, T.; Sieper, J.
Abstract : Background: There is still limited knowledge about early axial spondyloarthritis (axSpA) patients in primary rheumatology care. Methods: Rheumatologist from n=70 study centres across Germany recruited patients with spondyloarthritis (SpA) diagnosed for the first time (time since diagnosis <1 year) over three consecutive years. Patients were evaluated and documented regarding clinical, laboratory and imaging characteristics, fulfilment of ASAS classification criteria and treatment. In addition, participating centres (n=36) documented the frequency of newly diagnosed SpA among all patients seen for the first time in their practice in one week. Results: A total of 427 newly diagnosed SpA patients were recruited. 342 patients (mean age 38.9 years, range 18–73; 55.3% males) had a new diagnosis of axSpA (mean symptom duration 81.5 months (range 0–599)) and are presented here in more detail. 36.5% were classified as radiographic axSpA according to the modified New York criteria and 19.3% were imaging (magnetic resonance imaging and X-rays) negative. The laboratory, clinical and imaging characteristics of these patients are shown in the table 1. 85.4% of these patients diagnosed as axSpA by the rheumatologist fulfilled the ASAS classification criteria. 69.9% were treated with NSAIDs, 3.8% with conventional DMARDs and 1.2% with biologics when seen for the first time by the rheumatologist. The therapy has been continued or changed as follows by the rheumatologist at first visit after making the diagnosis of axSpA: NSAIDs in 80.7%, conventional DMARDs in 8.8% and biologics in 10.5%. However, additional treatment with biologics might be initiated at follow-up visits. The proportion of SpA patients among all newly diagnosed patients with rheumatic conditions documented in one week was 17.5% (10.1% axSpA and 7.4% peripheral SpA). Conclusions: The characteristics of axSpA patients seen in primary rheumatology practices are comparable to what has been reported. The majority of patients are still in the stage of non-radiographic axSpA when diagnosed first and the majority of patients have active MRI inflammation in the sacroiliac joints but not in the spine. In about 10% of patients a TNF-blocker was started already at first visit. Disclosure of Interest: D. Poddubnyy Grant/research support from: AbbVie, MSD, Novartis., Consultant for: AbbVie, BMS, Boehringer, MSD, Novartis, Pfizer, and UCB., Speakers bureau: AbbVie, BMS, Janssen, MSD, Novartis, Pfizer, and UCB., E. Edelmann Consultant for: AbbVie, Boehringer-Ingelheim, Lilly, Mundipharma, MSD, Novartis, Pfizer, Roche, UCB., V. Rios Rodriguez Consultant for: Abbvie, MSD and Novartis., S. Sartingen Shareholder of: AbbVie Inc., Employee of: AbbVie Deutschland GmbH and Co. KG., T. Mosch Shareholder of: AbbVie Inc., Employee of: AbbVie Deutschland GmbH and Co. KG., J. Sieper Grant/research support from: AbbVie, Merck, and Pfizer., Consultant for: AbbVie, Janssen, Lilly, Merck, Novartis, Pfizer, and UCB., Speakers bureau: AbbVie, Janssen, Merck, Novartis, Pfizer, Roche, and UCB.